Термоэлектрический прибор для медико-биологической экспресс-диагностики - Ashcheulov, A. A.; Kushnerik, L. Ya. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The possibility of creating thermoelectric sensors for diagnosing symmetrically located points on the human body has been investigated. The design features of the developed sensors are described, and the results of their clinical trials are presented. The operating principle of the device for rapid diagnosis is described. Its potential is demonstrated.